Activity of cefepime/taniborbactam and comparators against whole genome sequenced ertapenem-non-susceptible Enterobacterales clinical isolates: CANWARD 2007–19. Issue 1 (7th February 2022) - Golden, Alyssa R.; Baxter, Melanie R.; Karlowsky, James A.; Mataseje, Laura; Mulvey, Michael R.; Walkty, Andrew; Bay, Denice; Schweizer, Frank; Lagace-Wiens, Philippe R. S.; Adam, Heather J.; Zhanel, George G.
Abstract: Objectives: This study assessed in vitro activities of cefepime/taniborbactam and comparator antimicrobial agents against ertapenem-non-susceptible Enterobacterales (ENSE) clinical isolates collected from the CANWARD study 2007–19, and associations between MIC and various mechanisms of β-lactam resistance identified using WGS. Methods: A total of 179 ENSE (MIC ≥ 1 mg/L) isolates underwent susceptibility testing using reference CLSI broth microdilution. WGS was performed using the Illumina NextSeq platform. Carbapenemases, ESBLs and other β-lactamases were identified using ResFinder 4.0. Alterations in ompC / F and ftsI (PBP3) were identified by comparing extracted sequences to the appropriate NCBI reference gene. Porin alterations were analysed with Provean v1.1.3. Specific alterations of interest in PBP3 included a YRIN or YRIK insertion after P333. Results: Cefepime/taniborbactam was highly active (MIC50 /MIC90, 0.5/2 mg/L; 177/179 isolates inhibited at ≤ 8 mg/L) against ENSE with various antimicrobial resistance phenotypes. Thirteen (7.3%) of the 179 ENSE isolates demonstrated cefepime/taniborbactam MIC values ≥ 4 mg/L and possessed combinations of β-lactam resistance mechanisms, including a carbapenemase and/or ESBL and/or other β-lactamase genes, as well as alterations in OmpC and/or OmpF and/or PBP3. Of the two Escherichia coli isolates that demonstrated a cefepime/taniborbactam MIC of 32 mg/L, one possessed NDM-5, OXA-181 and TEM-1B, an OmpC alteration and P333_Y334insYRIN in PBP3, while the second contained CTX-M-71, a truncated OmpF and a large alteration in OmpC (F182_R195delinsMTTNGRDDVFE). Conclusions: Cefepime/taniborbactam was highly active against ENSE with various antimicrobial resistance phenotypes/genotypes. ENSE isolates with cefepime/taniborbactam MIC values ≥ 4 mg/L possessed combinations of β-lactam resistance mechanisms, including β-lactamase genes, as well as alterations in OmpC and/or OmpF and/or PBP3.